PENINGKATAN AKTIVITAS DAN HASIL BELAJAR FISIKA MATERI HUKUM TERMODINAMIKA MENGGUNAKAN APLIKASI ZOOM CLOUD MEETINGS PADA SISWA KELAS XI IPA-1 SMA NEGERI 1 SIBORONGBORONG SEMESTER 2 TAHUN PELAJARAN 2020/2021 - Masdollar Lumbantoruan (Program Studi Pendidikan Matematika, Fakultas Keguruan dan Ilmu Pendidikan Universitas Cokroaminoto Yogyakarta, 2021)
The research aims to improve the activity and learning outcomes of physics subject matter for the law of thermodynamics for class XI IPA-1 SMA Negeri 1 Siborongborong Semester 2 of the 2020/2021 academic year. The research was carried out in two cycles and each cycle consisted of four stages, namely planning, action, observation, and reflection. The research subjects were 36 students. Data collection techniques using the method of observation, documentation and tests. Data validity through triangulation. Data analysis with qualitative descriptive technique. The results showed that the activity of students in the initial study was 36.11% or 13 students became 72.22% in the first cycle or 26 students, and in the second cycle it became 94.44% or 34 students were declared complete. The increase in the average value in the initial study from 63.33 to 73.33 in the first cycle, and in the second cycle to 84.17 and an increase in learning completeness from 10 students or 27.78% to 21 students or 58.33% and 32 students or 88.89% in the second cycle.